Filsafat Cinta Menurut Pemikiran Hamka - Damanik, Nurliana (UIN Sumatera Utara, 2025)
Prof. Dr. Haji Abdul Malik Karim Amrullah or often called Buya Hamka. Buya Hamka is an Indonesian intellectual figure who has down-to-earth thoughts and a vision of the future. Happiness or joy is a state of mind or feeling characterized by sufficiency to pleasure, love, satisfaction, enjoyment, or intense joy. Various approaches to philosophy, religion, psychology, and biology have been carried out to define happiness and determine its source. Happiness is the inner realm and not the physical realm. Because of the inner and not physical nature, happiness can be felt by anyone regardless of their social background. Happiness can also be felt by the rich, the poor, officials or ordinary people. This is what our religion teaches that happiness and material things are different, not directly proportional. It is not necessary that every poor person cannot meet the criteria for happiness, it is not necessary that rich people always feel happiness. Al-ghina ghina an-nafs, the real wealth is this inner wealth.